Accessibility of ophthalmic healthcare for residents of an offshore island—an example of integrated delivery system - Chen, Li-Ju (BMC Health Serv Res, 2016)
BACKGROUND: To assess the utilization of and satisfaction with ophthalmic healthcare provided by integrated delivery system (IDS) since 2000 and vision-related quality of life (VRQoL) for residents of an offshore island of Taiwan. METHODS: Facilitators interviewed residents (age ≥ 50 years) with the 25-item National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) for VRQoL and a questionnaire on clinical information, ophthalmic care utilization and satisfaction. RESULTS: A total of 841 participants (response rate 93.4 %, 841/900) completed the questionnaire survey. Mean age was 63.7 (±10. 7) years. The common eye diseases were cataract (44.7 %), dry eye (15.5 %), and glaucoma (8.7 %). Among the participants, 61.0 % sought ophthalmic care under the IDS in the past year and 17.6 % experienced unmet ophthalmic needs in the past 6 months. Satisfaction with ophthalmic care under the IDS was 88.1 %. Determinants of dissatisfaction under the IDS were distance to healthcare facility and VRQoL. Predictors of VRQoL included age, residential area, marital status, occupation, comorbid condition, commercial insurance, household income, cataracts and glaucoma. CONCLUSIONS: The implementation of IDS improves accessibility of ophthalmic care for residents of an offshore island. Geographic proximity to avail healthcare facility and VRQoL affect satisfaction with the IDS.